FREQUENCY ANALYSIS OF VICORISTAN LETTERS OF UKRAINIAN MOVIE - Arkhipova, E. A.; Zhuravlev, V. N. (Radio Electronics, Computer Science, Control, 2024)
In this paper is considered unresolved tasks in the research field of the communications speech quality. The frequency analysis of the Ukrainian letters usage for total amount of texts about 580 thousand signs in art, publicistic and technical area is carried out. For the first time it is received the frequency histogram of letters usage of the Ukrainian alphabet for modern language.